Nitric Oxide Involvement in Cardiovascular Dysfunctions of Parkinson Disease - Martins-Pinge, Marli Cardoso; de Jager, Lorena; de Campos, Blenda Hyedra; Bezerra, Lorena Oliveira; Turini, Pamela Giovana; Pinge-Filho, Phileno (Frontiers in Pharmacology, 2022)
Parkinson´s disease (PD) is characterized by the loss of dopaminergic neurons in the substantia nigra, causing motor changes. In addition to motor symptoms, non-motor dysfunctions such as psychological, sensory and autonomic disorders are recorded. Manifestations related to the autonomic nervous system include the cardiovascular system, as postural hypotension, postprandial hypotension, and low blood pressure. One of the mediators involved is the nitric oxide (NO). In addition to the known roles such as vasodilator, neuromodulator, NO acts as an important mediator of the immune response, increasing the inflammatory response provoked by PD. The use of non-specific NOS inhibitors attenuated the neurodegenerative response in animal models of PD. However, the mechanisms by which NO contributes to neurodegeneration are still not well understood. The literature suggest that the contribution of NO occurs through its interaction with superoxides, products of oxidative stress, and blocking of the mitochondrial respiratory chain, resulting in neuronal death. Most studies involving parkinsonism models have evaluated brain NO concentrations, with little data available on its peripheral action. Considering that studies that evaluated the involvement of NO in the neurodegeneration in PD, through NOS inhibitors administration, showed neuroprotection in rats, it has prompted new studies to assess the participation of NOS isoforms in cardiovascular changes induced by parkinsonism, and thus to envision new targets for the treatment of cardiovascular disorders in PD. The aim of this study was to conduct a literature review to assess available information on the involvement of nitric oxide (NO) in cardiovascular and autonomic aspects of PD.